Learning Problems of the Secondary And Junior College Learning Disabled Student: Suggested Remedies. - Kahn, Michael S. (Journal of Learning Disabilities, 1980)
Lists suggested remedies for dealing with learning problems of the secondary and junior college learning disabled students. Behavioral characteristics of learning disabled students; Classroom methods for circumventing learning problems.